2007
DOI: 10.1074/jbc.m700846200
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Lipophilic Peptidoglycan-related Molecules in Induction of Nod1-mediated Immune Responses

Abstract: Nod1 is an intracellular protein that is involved in recognition of bacterial molecules and whose genetic variation has been linked to several inflammatory diseases. Previous studies suggested that the recognition core of Nod1 stimulatory molecules is ␥-D-glutamyl-meso-diaminopimelic acid (iE-DAP), but the identity of the major Nod1 stimulatory molecule produced by bacteria remains unknown. Here we show that bacteria produce lipophilic molecules capable of stimulating Nod1. Analysis of synthetic compounds reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…The TAK1 inhibitor NG-25 (28), the IKKβ inhibitor BI605906 (20), KF-1B (29,30), MRT67307 (31), BIRB0796 (32), and PD0325901 (33) were synthesized as described. The TLR7 agonists, CL097 (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…The TAK1 inhibitor NG-25 (28), the IKKβ inhibitor BI605906 (20), KF-1B (29,30), MRT67307 (31), BIRB0796 (32), and PD0325901 (33) were synthesized as described. The TLR7 agonists, CL097 (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…1). In this context, FK565, FK156, and iE-DAP derivatives induced cross-presentation more efficiently than iE-DAP, probably, at least in part, because these molecules contain acyl residues conjugated to the core iE-DAP, which enhance host cell membrane permeability and, thereby, the ability to stimulate Nod1 (26,27). Consistent with previous findings (2-4), poly(I:C)-stimulated DCs also enhanced the cross-presentation of OT-I cells (Supplemental Fig.…”
Section: Nod Ligand Enhances Dc-mediated Cross-presentationmentioning
confidence: 99%
“…Furthermore, Nod1 stimulation contributes to adaptive immune responses, although the mechanism involved remains unclear (Fritz et al, 2007). In vitro studies have demonstrated that many bacteria express Nod1-stimulatory activity, which is highest in Bacillus species (Hasegawa et al, 2007). Moreover, infection of host cells by several pathogenic bacteria, including Shigella flexneri (Girardin et al, 2001), enteroinvasive Escherichia coli (Kim et al, 2004), Listeria monocytogenes (Park et al, 2007b) and Campylobacter jejuni (Zilbauer et al, 2007), results in Nod1-dependent NF-kB activation.…”
Section: Nod1 and Nod2mentioning
confidence: 99%